Preliminary Study on the State of Pre-Monsoon Time Climatic Comfort Over the Chitwan Valley, Nepal - Regmi, Ram Prasad (Himalayan Physics, 2015)
Available with full text. The Himalayan Physics Vol. 5, No. 5, Nov. 2014 Page: 59-68